Morfologia e dinâmica testicular em cutias (Dasyprocta prymnolopha) adultas - Menezes, D. J.A.; Silva, A. R.N.; Vieira, F. A.S. [UNESP]; Silva Neto, R. B.; Oliveira, M. F.; Illera, M. J.; Assis Neto, A. C.; Santos, J. R.S.; Carvalho, M. A.M. (FapUNIFESP (SciELO), 2017)
This study meant to characterize the morphology of the testicle from (Dasyprocta prymnolopha) agouti males, in order to collaborate with the knowledge of reproductive morphophysiology of the specie. Testicles were used from 47 animals aged between 1 and 2 years, homogeneous weight (2.08±0.23kg), coming from the Centre for the Study and Conservation of Wild Animals of Agricultural Sciences Center of the Federal University of Piauí. The structures were dissected, described and fragments were processed for light microscopy, and, subsequently, gonadal activity was evaluated. Testes were observed to be elongated ellipsoidal bodies that can be found in the groin or in the abdominal cavity, not having a clearly defined scrotum. We also could see parenchymal with standard histological characteristic for the mammalian body, with the identification of eight types of cell associations, characterized epithelium Seminiferous stages of the cycle, with lower and higher frequency of stages 3 and 5, respectively.
Testicular morphology and dynamic in adult agoutis (Dasyprocta prymnolopha)
Keywords: Histricomorpha; Reproduction; Rodent; Spermatogenesis